HEALTH NEEDS OF OLDER HOMELESS PERSONS WHO ARE TRANSITIONING FROM HOSPITAL TO SHELTER/HOUSING. (11th November 2018) - Canham, S; Davidson, S; Custodio, K; Mauboules, C; Good, C; Wister, A V; Bosma, H
Abstract: In Metro Vancouver (Canada) there has been a significant increase in homelessness among persons aged 55+. This group has worse health than the general population. Moreover, discharging homeless patients from hospital to community settings is difficult, particularly for older adults. To improve continuity of care and enhance outcomes for older homeless persons, a better understanding of the health supports required for discharge is needed. We conducted 40 in-depth interviews to capture the perspectives of housing and healthcare providers and persons with lived experience of homelessness to identify the health supports needed for these transitions. Thematic analysis revealed older adults are often discharged to inappropriate locations, such as shelters, given a lack of better options. Older adults experience vulnerability in shelter settings and face unique challenges in light of complex health issues. Recommendations for senior-specific shelter and transitional housing and services will be described.